(untitled) (International Journal of Food and Nutritional Sciences, 2021)
More complex food supply networks are a direct outcome of increased international trading in agricultural products. The food supply chain is rife with potential points of failure due to the wide variety of entities, processes, and localizations that might compromise food safety. Prior to this, food safety protocols primarily addressed the stages of manufacturing, processing, and sale. The logistics sector has mostly disregarded the importance of integrating the commodity flows component, which links the main phases. Because of this, there are gaps in knowledge that make it difficult for risk assessors to ensure the safety of consumers. We developed a conceptual framework (CF) to analyse the impact of global commodity flows on food safety and to map the study domain. We used agricultural bulk commodities (ABC) as an example. The foundation of the CF was a grounded theory-inspired qualitative text analysis of a wide range of literature reports. Presented below are the main concepts, both inside and outside of ABC flows, that are crucial for the logistical study of food safety. Concerns that arise from using these criteria are brought to light by the study. A universally accepted definition of food safety cannot be established, we conclude. Instead, our research showed that distinct levels of criteria are utilized to assess food safety: standards developed by scientists based on their knowledge and values and consumer-based criteria based on their knowledge and values that influence their behaviour. The food business and society at large place a high value on food safety as a means of protecting people’s lives and well-being. While no one can agree on a single definition of food safety, most research starts with the premise that we can objectively evaluate the presence or lack of food safety using facts from the natural sciences. From there, people may draw their own conclusions and opinions. Differences of opinion among scientists and an increasing amount of public discussion suggest that no one group has settled on a single definition of "safe" or "unsafe" behaviour. By classifying criteria from several research disciplines, this study presents a framework that differentiates evidence practices and characterizes food safety in a more generic sense. It uses plant protection items as an example. Further, within the framework of risk management, it aids experts in tackling complex food safety challenges.